Immunohistochemical characteristics of the nerve fibres of sow retractor clitoridis muscle - Botti, Maddalena; Ragionieri, Luisa; Gazza, Ferdinando; Minelli, Luisa Bo; Panu, Rino (Italian Journal of Anatomy and Embryology, 2012)
The occurrence of several biologically active neuropeptides (calcitonine gene-related peptide, leu-enkephaline, neuropeptide Y, substance P, and vasoactive intestinal peptide) or nitric oxide-synthesizing enzymes (neuronal nitric oxide synthase), tyrosine hydroxylase, vesicular acetylcholine transporter, and their co-localization with tyrosine hydroxylase were investigated by immunohistochemistry in the retractor clitoridis muscle of slaughtered sows. Single immunolabelling revealed that tyrosine hydroxylase and neuropeptide Y immunoreactive nerve fibres were the most numerous, followed by the neuronal nitric oxide synthase and calcitonine gene-related peptide immunoreactive ones, the vasoactive intestinal peptide, substance P and leu-enkephaline immunoreactive nerve fibres were few and vesicular acetylcholine transporter immunoreactivity were observed only in single fibres. Double immunolabelling revealed the only co-localization of tyrosyne hydroxylase with neuropeptide Y. The most reliable labelling of nerve fibres of the retractor clitoridis muscle was observed around blood vessels, followed by non-vascular smooth muscles. The present data indicate that the sow retractor clitoridis muscle receives nerve fibres that exhibit different chemical codes and, likely, differences in their chemical coding depend on the target-structure.